The influence of power and commitment to the implementation of strategic management in village government (study on village government in Sidoarjo district) - Purwanto, Purwanto; Sumiati, Sumiati; Djumahir, Djumahir (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2018)
Strategic management plays an important role in village governance to improve the quality of public services. The Village Government receives substantial funding but has not been followed by adequate strategic management governance. Changes in policy, environmental change and the ability to deliver better quality public services have become the demand for village governments to adapt their institutions for developments and changes. This research focuses on the influence of power and commitment on the application of Strategic Management in Village Government (Study on Village Government in Sidoarjo District). This study aims to explain whether power and commitment have a significant effect on strategic management in Village Government. The research was conducted by using questionnaires to test the research variables from Respondents. The results explain the influence of the two variables and the results are analyzed using WarpPLS. The results of this study indicate that the two variables positively affect the implementation of strategic management in village government. Expert and reverend based power and continuance commitment have a positive effect on the implementation of strategic management in village government. The results of this study will play a significant role in helping Village Governments analyze the factors that influence strategic management governance